Demokracja, rządy prawa i poszanowanie praw człowieka w aktywności Unii Europejskiej wobec Egiptu - Potyrała, Anna (Rocznik Integracji Europejskiej, 2015)
Contrary to expectations, the changes initiated by the ‘25 January Revolution’ have not strengthened democratic principles in Egypt. Therefore, the European Union and its member states have sought to support the stability of this state, promote democratic values and human rights. The purpose of this study is to analyse EU activities aimed at fostering the democratisation process in Egypt, as well as to assess these activities so far and identify the reasons for their ineffectiveness.